Coagulation Studies in Liver Disease - Hallén, Acke; Nilsson, Inga Marie (Thrombosis and Haemostasis, 1964)
Various caogulation factors were studied in 20 cases of liver cirrhosis for their possible diagnostic value. Special attention was given to determination of antithrombin (AT), and AT values were also studied in a series of hepatitis and obstructive jaundice.The P & P test was decreased in 75%, the factor V content in 83%, the factor IX content in 40% and the platelet count in 55% of the cases of liver cirrhosis.Increased fibrinolytic activity was noted in 5 cases. Only 2 cases had significantly decreased fibrinogen levels and most probably due to fibrinolysis. The AHF (f. VIII) level was slightly decreased in 2 cases, one of which had fibrinolysis, while the other had normal AHF levels.In 12 of 18 cases of liver cirrhosis the AT II and III was decreased and only in one case was it increased but the decreased values deviated only slightly from the normal range. AT II and III in 23 cases of obstructive icterus and in 19 cases of hepatitis gave practically normal values.Judging from our results determination of P & P and factor V is valuable in the diagnosis of liver cirrhosis. Determination of AT II and III by use of an improved method proved not to give any further help in the diagnosis of liver cirrhosis or the differential diagnosis between cirrhosis, hepatitis and obstructive jaundice.